Applied electrochemical biosensor based on covalently self assembled monolayer at gold surface for determination of epinephrine in the presence of Ascorbic acid - Moghadam Zohreh; Sayed Mehdi Ghoreishi; Mohsen Behpour; Motaghedifard Mohammadhassan (Arabian Journal of Chemistry, 2017)
In this paper, a new electrochemical sensor for the determination of epinephrine (Epi) in the presence of ascorbic acid (AA) is described. The characterization of Au TMBH self-assembled monolayer modified electrode (TMBH SAM-ME) was investigated by cyclic voltammetry (CV) using the [Fe(CN)6]−3/−4 redox couple. The mediated oxidation of Epi at the modified electrode was investigated by voltammetric methods and the values of transfer coefficient (α), the ionic exchanging current density (io), catalytic rate constant (kh) and diffusion coefficient (D) were calculated. By double potential step chronoamperometric experiments (DPCHA) at the modified electrode was obtained two linear segments of 1.7–24.9 μM and 24.9–91.7 μM by a detection limit (3σ) of 0.19 ± 0.01 μM for Epi. The advantages of this modified electrode were reproducibility and repeatability, stability and anti fouling effect against oxidation products of Epi at the surface of TMBH SAM-ME. Finally, the modified electrode was shown agreeable responses to recovery of Epi from real sample solutions by standard addition method.